The Relationships between Anti-Thyroid Peroxidase (Anti-TPO) and Inhibin-B as Predictor Biomarkers for Female Infertility - Mamitha, Zahraa Abd Al-Amir Jalil; Al-Fatlawi, Abeer Cheaid Yousif; Al-Tamimi, Manal Nasih Ahmed Hamdan (HAYATI Journal of Biosciences, 2025)
Anti-thyroid peroxidase is an autoantibody generated by the immune system, its primary function is target and neutralize the enzyme thyroid peroxidase, is essential for production of thyroid hormones. Inhibin-B is a peptide belonging to TGF-β family produced by granulosa cells of the growing follicle cohort. It reflects the health of follicles, their overall numbers. The objective of this article is evaluation of Anti-TPO, Inhibin-B for female infertility. A case-control study includes 120females between 20-45 years divided into 60 apparently healthy females used as controls and 60 infertile females distributed 37 with Polycystic ovarian syndrome, 23 with Premature ovarian failure. Serum levels of Anti-TPO, Inhibin-B, LH, FSH, Testosterone, Prolactin and Estrogen were all measured using an ELISA assay. Inhibin-B, Anti-TPO higher in patients than in controls. Inhibin-B significantly increases(p≤0.0001) in PCOS above and under 40years (273.55±75.25 pg/mL), (234.91±52.43 pg/mL), but decreases in POF (18.96±1.21 pg/mL) than in controls (35.58±10.48 pg/mL), (42.04±10.04 pg/mL). AntiTPO increases in PCOS and POF above and under 40 years (16.08±2.14 ng/mL), (17.63±1.93 ng/mL), (14.72±1.19 ng/mL) than in controls(5.92±0.99 ng/mL), (5.93±0.84 ng/mL). The levels of FSH, Prolactin, Testosterone, Estrogen and LH were increased (p≤0.0001) in PCOS, POF as in controls. The results showed a negative correlation (p≤0.0001) between Inhibin-B, Anti-TPO (r = -0.520) in PCOS. The Receiver operating characteristic (ROC) analysis demonstrated Inhibin-B 95%CI:0.907-1.000; P-value:0.001; Cutoff Point:77.347; AUC:95.417% with Sensitivity to Specificity 91.667-98.333%; Accuracy: 95.000%. Anti-TPO 95% CI: 0.907-1.000; P-value: 0.001; Cutoff Point: 9.306; AUC: 98.861% with Sensitivity to Specificity 96.676-96.667%; Accuracy: 97.000%. Anti-TPO, Inhibin-B are useful biomarkers for evaluating fertility status and ovarian health, can used as sensitive indicators for early diagnosis of PCOS and POF in women of reproductive age.